Proses Alignment Mesin Uji Rolling Resistance Menggunakan Ban Referensi Dengan Metode Regresi Linier Sederhana Pada Lab X Dalam Pemenuhan Regulasi ISO 28580 - Jawad, Aod Abdul; Mulyono, Agus; Zulziar, Marjuki (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2022)
Rolling resistance is the force used by the wheel against the direction of motion, equal to the force required to move the wheel forward. The research was conducted at the Tire Testing Laboratory of PT. Gajah Tunggal Tbk at Jalan Gatot Subroto km7 Jatiuwung Tangerang City. To support product development and certification, PTGT currently has 2 Rolling resistance (RR) machines.The purpose of this study is that the measurement results in the Testing at the Gajah Tunggal tire testing laboratory can be accepted and recognized internationally, the RR Testing machine at the PTGT tire testing laboratory must be aligned with the reference RR engine as specified in the regulations. described in ISO 28580 clause 10. Alignment Procedures and Measurement Machine Monitoring Requirements to be followed to harmonize measurement results and allow direct inter-laboratory comparisons. This procedure shall be applied to any measuring machine whose results are claimed to conform to International Standards. The test results on the DRR-1 engine the lowest value is 6.97 and the highest value is 10.33 is 3.17 kg/ton. This maximum and minimum difference value also meets the predetermined target, which is approximately equal to 3kg/ton and the reproducibility rate is 0.015 kg/ton. The correlation value is indicated by R squared (R2), which is 0.9939 for the DRR-1 test machine. The DRR-1 rolling resistance machine complies with the regulations required by ISO 28580 and the measurement value of the machine is internationally accepted and recognized.